(untitled) (Ameghiniana, 2013)
On the western side of the Cerro Huantrai-co, North of the Neuquen Province, there are outcrops from freshwater and marine strata resting upon Cretaceous continental red beds and covered by basa1tic lavas and tuffs of Tertiary age, which are faulted forming a syncline and are intruded by basaltic dikes. The studied section comprises the freshwater and marine beds; with the first, composed by olive gray clays which contain freshwater ostracoda, beggins the Upper Cretaceous transgression followed by brackish to open marine sandy cha1ks, sandy and calcareous clays strata. For this part of the section it is proposed the name Huantrai-co Formation, which is separed in a lower freshwater member (Ievels CP-25 to CP-23) and an upper marine member (levels CP-22 to CP-ll). The Huantrai-co Formation is followed by the Roca Formation composed by cha1ks and sandy chalks. The Huantrai-co Formation represent in the Cretaceous basin an outher shelf subsidence area whereas the Roca Formation, in the Lower Tertiary, was deposited in a shallow sea. The micropa1eonto1ogica1analysis, shows a sharp faunistic break between the Huantrai-co and the Roca Formations, dated as Late Cretaceous (Lower and Midd1e Maastrichtian) and Early Tertiary (Lower Danian). The age, in the Cretaceous strata, is based especially on p1anktonic foraminifera and benthonic -foraminifera and ostracoda- associations. The Lower Tertiary p1anktonic assemb1age shows an early phylogenetically development; Globoconusa daubjergensis (Bronnimann ), 1acks sutura1 openings on the spira1 side, and Globorotalia pseudobulloides (P1ummer) and Subbotina triloculinoides (P1ummer) shown smooth walls. A hiatus. which comprises the Upper Maastrichtian, is registered. In the present paper are described and figured some new ostracoda species form the Cretaceous-Tertiary section in the Huantrai-co area.